2021
DOI: 10.46827/ejphs.v4i2.96
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Sexual Life of Menopausal Women: Scoping Review

Abstract: Background: WHO predicts that there will be a menopause explosion in 2030 with around 1.2 billion women aged over 50 years. Most of them (about 80%) live in developing countries. The population of postmenopausal women is increasing by about three percent every year. Although menopause is a normal condition, it turns out that not all women can accept this well, one of which is related to sexual problems. Objective: To determine the factors that influence the sexual life of menopausal women in various countries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“… 40 Therefore, it seems that implementing interventions to change intellectual content and negative feeling and focusing on mindfulness that includes identifying and accepting present experience to be useful, 41 especially for this group of women, whose population is expected to reach 1.2 billion by 2030. 41 , 42 Although there is a relationship between mindfulness and sexual satisfaction, 22 no studies have been conducted so far concerning the effects of mindfulness on sexual self-efficacy and sexual satisfaction in Iranian postmenopausal women. The present study is designed based on the following questions: (1) Can mindfulness-based education affect sexual self-efficacy after intervention?…”
Section: Introductionmentioning
confidence: 99%
“… 40 Therefore, it seems that implementing interventions to change intellectual content and negative feeling and focusing on mindfulness that includes identifying and accepting present experience to be useful, 41 especially for this group of women, whose population is expected to reach 1.2 billion by 2030. 41 , 42 Although there is a relationship between mindfulness and sexual satisfaction, 22 no studies have been conducted so far concerning the effects of mindfulness on sexual self-efficacy and sexual satisfaction in Iranian postmenopausal women. The present study is designed based on the following questions: (1) Can mindfulness-based education affect sexual self-efficacy after intervention?…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, these may be unexpected or worse than women have anticipated (Currie & Moger, 2019). Those that are commonly reported, and likely to play a part in women's friendships and/or partner relationships, include anxiety, depression, hot flushes, insomnia, night sweats, reduced interest in sexual activities, and vaginal dryness (e.g., Caico, 2011; Currie & Moger, 2019; Hinchliff et al, 2010; Nosek et al, 2012; Stephens, 2001; The Fawcett Society, 2022; Vidia et al, 2021). In a recent survey by The Fawcett Society, (2022), 77% of respondents reported that at least one symptom was “very difficult,” with the most common being difficulties with sleep (84%), brain fog (73%), and night sweats/hot flushes 2 (70%).…”
mentioning
confidence: 99%